Conjugation of a Cryptococcus neoformans-derived metalloprotease to antifungal-loaded PLGA nanoparticles treats neural cryptococcosis in an in vitro model - Dylan M. Lanser; Adam Turner; Noah Pacifici; Kiem Vu; Jamal Lewis; Angie Gelli (PLoS ONE, 2026)
Overcoming the blood-brain barrier to deliver therapeutics is a major hurdle in treating diseases of the central nervous system. We engineered 4-arm carboxyl terminated poly(D,L-lactide-co-glycolide) nanoparticles with the fungal metalloprotease Mpr1, an enzyme utilized by the neurotropic pathogen Cryptococcus neoformans ( Cn ) to cross the blood-brain barrier. Nanoparticles were prepared using a modified single emulsion solvent evaporation technique, and characterized in terms of shape, size, zeta potential, encapsulation efficiency, and toxicity to brain microvascular endothelial cells. Mpr1-functionalized nanoparticles had increased penetration over non-functionalized nanoparticles in an in vitro model of the blood-brain barrier. When encapsulating amphotericin B, a potent antifungal drug, Mpr1-functionalized nanoparticles reduced fungal burden in an in vitro model of neural cryptococcosis. Loaded nanoparticles also had an 8-fold lower minimum inhibitory concentration against Cn and Candida albicans ( Ca ) compared to unencapsulated amphotericin B. Results indicate that Mpr1-coating of polymeric nanoparticles is a promising strategy to enhance drug delivery to the brain.